PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Fauziah, Deva; Sahara, Lia Ira (Publika Citra Media, 2025)
This study aims to analyze the effect of independent commissioners, audit committees, and company size on tax avoidance. The type of research used in this study is quantitative. The data source used is secondary data, namely annual financial reports obtained from the Indonesia Stock Exchange (IDX). The population used in this study consists of non-cyclical industrial sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The sample selection technique used is purposive sampling, resulting in 31 companies over five years, with a total sample size of 155 data points. The results of this study show that independent commissioners, audit committees, and company size simultaneously influence tax avoidance. However, independent commissioners and audit committees have no significant effect on tax avoidance, while company size significantly influences tax avoidance.